2017
DOI: 10.1007/s12034-017-1511-0
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring the bandgap and magnetic properties by bismuth substitution in neodymium chromite

Abstract: The intrinsic distortions present in rare-earth orthochromites (RCrO 3) observed from lanthanum to lutetium (in R-site) can influence the magnetic properties like Neel transition and weak ferromagnetic coupling. A nonmagnetic cation with similar ionic radius would be a suitable candidate to engineer the inherent distortions of particular orthochromite. In this study, bismuth (Bi 3+) with a 6s 2 lone pair was chosen to substitute in neodymium (Nd 3+) site of NdCrO 3 (NCO) to tailor the intrinsic structural dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 43 publications
0
1
0
Order By: Relevance
“…It is found that for U =3.50 eV (for Cr/Fe), the calculated band gaps for NdCrO 3 and NdFeO 3 matched well with experimental values. [63][64][65] For the same value, i.e. U Cr =U Fe =3.50 eV, a band gap of 1.82 eV has been obtained for double perovskite Nd 2 CrFeO 6 .…”
Section: -Type Afm (A-afm) (C) C-type Afm (C-afm) and (D) G-type Afm ...mentioning
confidence: 72%
“…It is found that for U =3.50 eV (for Cr/Fe), the calculated band gaps for NdCrO 3 and NdFeO 3 matched well with experimental values. [63][64][65] For the same value, i.e. U Cr =U Fe =3.50 eV, a band gap of 1.82 eV has been obtained for double perovskite Nd 2 CrFeO 6 .…”
Section: -Type Afm (A-afm) (C) C-type Afm (C-afm) and (D) G-type Afm ...mentioning
confidence: 72%
“…From Fig. (7) is attributed to the vibrational motion of O1 and A along the x-axis, B 2g (5) describes the vibration of A-cation along the x-axis, Ag( 6) is associated with the in-phase rotational vibration of the CrO 6 octahedra around the y-axis, B 2g (6) corresponds to the vibration of A-cation and O1 along the z axis, B 1g (3) is ascribed to the out of phase octahedral rotation around the x-axis, the A g (4) phonon mode involves mixed vibrations of A-cation and O1 along the z-axis (A(z),O1(-z)), A 3g (4) is associated with the out-of-phase O2 scissor-like vibration and finally, B3g(2) is related to the anti-stretching vibration mode of O1 and O2 atoms [2,22,50].…”
Section: Raman Analysismentioning
confidence: 99%
“…Among various chromium oxides, HoCrO 3 is the most fascinating compound that has attracted great attention due to its rich structural, magnetic and magneto-caloric properties [2,3,7,20,22], but to our knowledge, the crystalline structure and many physical phenomena are far from clearness. On the other hand, the possibility to improve the physical properties with a partial R-site ionic substitution has motivated us to study the mixed valence chromitesHo 1-x Ba x CrO 3…”
Section: Introductionmentioning
confidence: 99%